FORMATISASI ONTOLOGI MANAJEMEN DAKWAH - ., Fahriansyah (UIN Antasari Banjarmasin, 2017)
When viewed in terms of elements of da'wah combined with the ontology of general management, the study area of da'wah management as a whole is 80 format. And when viewed in terms of the combination of da'wah interaction with the ontology of general management, then obtained 96 formulation format, so that the total format of ontology of da'wah management is 176 formulations ontology format.